Understanding Drug Use in Meghalaya: A Drug Users’ Perspective - Melari Shisha Nongrum; Carinthia Balabet Nengnong; Mattimi Passah; Bethabara Decruse; Wilson Dohling; Safeeda G. Warjri (Indian Journal of Public Health, 2025)
Despite being considered a low prevalence state for illicit drug use in 2005, presently Meghalaya faces heightened vulnerability to drug use. The absence of updated data in Meghalaya underscores the necessity for this study to profile drug users. A qualitative descriptive approach was adopted; 128 opioid substitution therapy clients and 17 service providers from three districts of Meghalaya were interviewed. Drug users were generally males with low educational attainment and 80% working in the unorganized sector. A quarter started drug use during their school years. The reasons for drug initiation are curiosity and experimentation, family problems, peer pressure, and de-stressing. Heroin, the most injected drug, accounted for a daily average expenditure of ‘500–’2000. The age of initiation of drugs is lower than in other states, thus warranting the need for enhanced sensitization about drug risks among school adolescents, youth, and the unorganized employment sector.